(untitled) (International Seven Journal of Health Research, 2023)
Introduction: The study and teaching of human anatomy are important processes to understand how the human body presents itself and relates to other species. Osteology techniques are important for the classification of anatomical variations, scientific research tools and didactic use, and are performed through the physical, chemical or biological cleaning of bones to preserve the skeleton. Objective: To prepare, conserve, describe and catalog human bones from the Human Anatomy Laboratory of the Regional University Center of Espírito Santo do Pinhal, UniPinhal. Method: 50 complete human skeletons were donated to UniPinhal’s Human Anatomy Laboratory and underwent a process of general and specific cleaning, disinfection, bleaching, drying, description, cataloging in its own database, conservation and storage. Result: All 50 skeletons underwent all processes, with 30% in good condition, 55% in medium or poor condition and 15% presenting pathological findings, such as bone malformations, fractures and vicious bone consolidation. The mean age at death was 64 ± 16 years. Most were male (67%, n = 33) and declared white (57%, n = 28). The most common cause of death was septic shock (31%, n = 15) and an estimated 40% (n = 20) of deaths were of unnatural causes. A total of 5729 bones were cataloged in the database. Conclusion: The male skeletons and the color declared as white are the largest number in the ossuary, and a third were in good condition for use in practical classes, scientific research, anatomical and forensic studies by students of Health courses.